A numerical study of gyres, thermal fronts and seasonal circulation in austral semi-enclosed gulfs - Tonini, Mariano Hernan (2013)
This article analyses the results from a high resolution numerical model of the North Patagonian Gulfs(San Matías Gulf, SMG; Nuevo Gulf, NG; and San José Gulf, SJG), a region of the South Western Atlantic Shelf that has long been recognized for its high productivity and biodiversity. The aim of the study is to explore the physical processes that control the mean circulation and its seasonal variability with focus on the generation of recirculation features (gyres) and frontal structures. The numerical results showed that both tidal and wind forcing significantly contribute to delineate the frontal structures and the seasonal circulation in the North Patagonian Gulfs. The overall summer circulation pattern in SMG is dominated by two strong cyclonic subgyres in the northern and southern sectors while NG showed only one gulf-wide cyclonic gyre. The northern subgyre in SMG and the NG gyre are caused by the interaction of the tides and the evolving stratification driven by surface heat and freshwater fluxes. A series of sensitivity experiments showed that the formation and intensity of a summer zonal front in SMG is controlled by the wind-driven advection of cold waters from a homogenized pool generated by intense tidal mixing in the inner continental shelf (east of Valdés Península). From April to August, when winter erodes the stratification, the northern SMG subgyre and the NG gyre spin down and gradually shrink in size. At this time of the year, the western SMG and NG are occupied by an anticyclonic gyre driven by intense westerlies. In contrast, the mean circulation in SJG is dominated year-round by a pair of strong counterrotating eddies produced by tidal rectification.